Developing supplementary materials for descriptive text writing using Ispring Quizmaker - Intra Wahyul Utami; Farina Tazijan; Eni Rosnija (Journal of English Language Teaching Innovations and Materials (Jeltim), 2022)
This research was conducted to develop supplementary materials to support writing on descriptive text in companion to the English textbook for Seventh Grade. This research is qualitative based, and the method adopted is by development research. The researcher used the ADDIE model as the model of development of this research. However, due to time limitations to accomplish all steps, this research only implemented three phases: analyzing, designing, and developing (ADD). This research used the semi-structured interview as the data collection technique and an interview guideline as the tool of data collection. The data of the analyzing step of this research were analyzed using the thematic analysis technique. The participant of this research was an English teacher of SMP Kemala Bhayangkari Kubu Raya. The product was developed using Ispring Quizmaker. During the process of Designing and Developing, the researcher evaluated the product of this research using the criteria of good materials by Bugler et al. (2017). In conclusion, the development of supplementary material for descriptive text writing (SEASON) as the product of this research has met the criteria of good materials.